A New Tridentate Sulfur Receptor as a Highly Sensitive and Selective Fluorescent Sensor for Cu2+ Ions. Issue 11 (22nd July 2013) - She, Haiying; Song, Fengling; Xu, Juan; Xiong, Xiaoqing; Chen, Gengwen; Fan, Jiangli; Sun, Shiguo; Peng, Xiaojun
Abstract The introduction of Lawesson′s reagent into a bis‐rhodamine spirolactam system afforded a new fluorescent sensor for Cu2+ ions, SRR, which contained a new tridentate sulfur ligand. SRR showed excellent specificity for Cu2+ ions over other cations (including Cu+, Hg2+, and Fe3+), very high sensitivity (10 nM), and a rapid response time (3 min). The detection mechanism was investigated by 1H NMR, 13C NMR, 31P NMR, and ESR spectroscopy, MS, and Gaussian calculations. Coordination of a Cu2+ ion to the tridentate sulfur ligand, which promotes ring‐opening of the rhodamine groups, followed by a spontaneous reduction reaction (Cu2+ into Cu+), has been proposed as the sensing mechanism.